2007
DOI: 10.1021/mp0700357
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sandwich-Cultured Hepatocytes To Evaluate Impaired Bile Acid Transport as a Mechanism of Drug-Induced Hepatotoxicity

Abstract: Drug-induced liver toxicity is a significant problem in drug development and clinical practice, yet its mechanisms are not well understood. Growing evidence suggests that inhibition of bile acid transport may be one mechanism of hepatotoxicity. A number of hepatic transporters work in concert to transport bile acids and xenobiotics from blood to bile, and many drugs have been shown to perturb this process with detrimental consequences. Hepatocytes cultured in a sandwich configuration maintain transporter activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
65
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 47 publications
9
65
0
Order By: Relevance
“…Interestingly, BEI value for CF in HepaRG cells (34.4 %) was nearly identical to CF BEI value reported in sandwich-cultured human hepatocytes (BEI=34%) (Hoffmaster et al, 2004), which suggests that MRP2 is similarly active in these primary human hepatocytes and in HepaRG cells. By contrast, taurocholate BEI values in sandwich-cultured human hepatocytes (around 70-75%) (Marion et al, 2007) are rather higher than that found in HepaRG cells (BEI=29.2%), which likely indicates a lower BSEP activity in HepaRG cells, consistent with the down-regulation of BSEP mRNA expression observed in these hepatoma cells (Fig. 1B).…”
Section: Resultssupporting
confidence: 61%
“…Interestingly, BEI value for CF in HepaRG cells (34.4 %) was nearly identical to CF BEI value reported in sandwich-cultured human hepatocytes (BEI=34%) (Hoffmaster et al, 2004), which suggests that MRP2 is similarly active in these primary human hepatocytes and in HepaRG cells. By contrast, taurocholate BEI values in sandwich-cultured human hepatocytes (around 70-75%) (Marion et al, 2007) are rather higher than that found in HepaRG cells (BEI=29.2%), which likely indicates a lower BSEP activity in HepaRG cells, consistent with the down-regulation of BSEP mRNA expression observed in these hepatoma cells (Fig. 1B).…”
Section: Resultssupporting
confidence: 61%
“…The biliary excretion of micafungin was inhibited by 90% with the Bsep inhibitor taurocholate (Marion et al, 2007) and by ϳ50% with GF120918 (10 M), a known inhibitor for P-gp and BCRP at this concentration (Ahmed-Belkacem et al, 2006) (Fig. 5A).…”
Section: Resultsmentioning
confidence: 95%
“…Because sandwich-cultured hepatocytes [(SCH) B-CLEAR; Qualyst, Inc., Durham, NC] maintain the expression and function of key uptake and efflux transporters relative to in vivo, it is the most relevant system to evaluate and predict the potential of a compound to cause transporter-based liver toxicity. Several reports have described the use of SCH to assess the effect of compounds on the inhibition of bile acid transport, albeit using different methodologies (Kostrubsky et al, 2003(Kostrubsky et al, , 2006Kemp et al, 2005;McRae et al, 2006;Marion et al, 2007). For example, Kostrubsky et al (2006) used SCH to evaluate the potential of drugs to inhibit bile acid transport.…”
mentioning
confidence: 99%